Teachers Strategies In Teaching Writing Descriptive Text At Mts N Sukoharjo In 2015/2016 Academic Year - Ichsan Raharjanto, Fadholi Ichsan, Mauly Halwat Hikmat, Ph. D (2016)
The objectives of the study are to describe teacher's strategies in teaching writing descriptive text at MTs N Sukoharjo in 2015//2016 academic year. There are three components of teaching learning process that the writer analyzes, namely: 1) the teacher's strategies in teaching writing descriptive text, 2) the application of strategies, and 3) the problems face by the teacher's in teaching writing descriptive text. This study is descriptive qualitative research. The data are taken from observation, interview, and document. In collecting the data, the writer employs observation and interview. The technique for analyzing data is data reduction, data display, and conclusion and verification. The results of this study are the strategies used by the teacher in teaching writing descriptive text are applying cooperative learning, and discussion, by making a group, and analyzing the picture. There are three problems faced by the students, namely: vocabulary problem, structure problem, and generic structure problem.